Strategi Kelas Ramah Anak dan Pengaruhnya terhadap Kesejahteraan Siswa di SD Negeri 5 Bringin - Siti Khumaidah; Naila Khoirun Nisa; Rini Fuji Lestari; Muhammad Safaruddin Najwa; H. Nur Rohman (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to describe the child-friendly classroom strategies implemented at SD Negeri 5 Bringin and their impact on student well-being. A child-friendly classroom is an educational approach that emphasizes the creation of a safe, comfortable, inclusive, and participatory learning environment, supporting students' emotional and social development optimally. This research employed a descriptive qualitative method with data collection techniques including observation, interviews, and documentation. The research subjects were students directly involved in the implementation of the child-friendly classroom, selected through purposive sampling. The results showed that child-friendly classroom strategies were actively implemented by teachers, involving students in planning and learning activities, and fostering good communication with parents. These strategies positively impacted student well-being, as reflected in increased feelings of safety, self-confidence, emotional regulation, and the quality of social interactions among students in the school environment. This study is expected to serve as a reference for teachers and schools in developing child-friendly learning environments to support students' holistic well-being.